Pengembangan Bahan Ajar Matematika Falak untuk Mahasiswa di UIN Sayyid Ali Rahmatullah Tulungagung - Cholis, Nur; Sholihah, Farid Imroatus; Krisno Wicaksono, Yudi (Lattice Journal : Journal of Mathematics Education and Applied, 2024)
Mathematics learning in higher education, especially in the Mathematics Education Study Program of the Faculty of Tarbiyah and Teacher Training, UIN Sayyid Ali Rahmatullah Tulungagung, has not fully accommodated the religious context, especially in astronomy. This causes students to feel difficult and less motivated to study astronomy. This study focuses on the integration of mathematics and astronomy in teaching materials. The integration effort then resulted in the research objective, namely to develop teaching materials that integrate mathematical concepts with astronomy, so that it can improve students' understanding and motivation in learning. The type of research used is development (R&D) with the ADDIE model which includes five stages: analysis, design, development, implementation, and evaluation. The results of the study show that the development of teaching materials that integrate mathematics and astronomy is categorized as effective in improving students' understanding and interest. The resulting textbooks not only contain theory, but also practical applications and Islamic values. The integration of mathematics and astronomy in teaching materials has proven to be effective in improving the quality of learning. The development of this textbook is expected to be a reference for teachers and help students understand complex concepts, as well as instill religious values ​​in the learning process.   Pembelajaran matematika di perguruan tinggi, khususnya di Program Studi Tadris Matematika Fakultas Tarbiyah dan Ilmu Keguruan UIN Sayyid Ali Rahmatullah Tulungagung belum sepenuhnya mengakomodasi konteks keagamaan, terutama dalam ilmu falak. Hal ini mengakibatkan mahasiswa merasa kesulitan dan kurang termotivasi untuk mempelajari falak. Penelitian ini berfokus pada integrasi antara matematika dan ilmu falak dalam bahan ajar. Usaha integrasi tersebut kemudian menghasilkan tujuan penelitian yaitu untuk mengembangkan bahan ajar yang mengintegrasikan konsep-konsep matematika dengan ilmu falak, sehingga dapat meningkatkan pemahaman dan motivasi mahasiswa dalam belajar. Jenis penelitian yang digunakan adalah pengembangan (R&D) dengan model ADDIE yang meliputi lima tahap: analisis, desain, pengembangan, implementasi, dan evaluasi. Hasil penelitian menunjukkan bahwa pengembangan bahan ajar yang mengintegrasikan matematika dan ilmu falak masuk kategori efektif dalam meningkatkan pemahaman dan minat mahasiswa. Buku ajar yang dihasilkan tidak hanya berisi teori, tetapi juga aplikasi praktis dan nilai-nilai Islam. Integrasi antara matematika dan ilmu falak dalam bahan ajar terbukti efektif dalam meningkatkan kualitas pembelajaran. Pengembangan buku ajar ini diharapkan dapat menjadi referensi bagi pengajar dan membantu mahasiswa dalam memahami konsep-konsep yang kompleks, serta menanamkan nilai-nilai keagamaan dalam proses belajar.